2022
DOI: 10.1021/acs.iecr.2c03344
|View full text |Cite
|
Sign up to set email alerts
|

Synergistically Enhanced Long-Term Effectiveness and Combustion Performance of Aluminum Nanoparticles by Partially Fluorinating External Alumina Shell

Abstract: Aluminum (Al) particles, especially nanosized Al (n-Al), are extremely liable to deteriorate when exposed to air during the preparation and storage process, which seriously threatens their inherent energy density and limits their combustion behavior. Until now, it is really challenging and urgent to improve the combustion performance without sacrificing the original high energy density. Here, in situ direct fluorination by utilizing F2/N2 mixed gas as a fluorinating agent was first applied to modify n-Al parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…FG also possesses an exceptional lubricant potential, with negligible interlayer interactions generated by repulsive forces between F atoms at the FG interface and can thus be utilised as a filler to change the wear resistance of polymers [81][82][83]. Hou K. et al [84] demonstrated that FG may be employed as an effective lubricant addition to improve lubricant wear resistance.…”
Section: Wear Resistance Of Fg/pi Composite Filmsmentioning
confidence: 99%
“…FG also possesses an exceptional lubricant potential, with negligible interlayer interactions generated by repulsive forces between F atoms at the FG interface and can thus be utilised as a filler to change the wear resistance of polymers [81][82][83]. Hou K. et al [84] demonstrated that FG may be employed as an effective lubricant addition to improve lubricant wear resistance.…”
Section: Wear Resistance Of Fg/pi Composite Filmsmentioning
confidence: 99%